Correlation between energy deposition and molecular damage from Auger electrons: A case study of ultra‐low energy (5–18 eV) electron interactions with DNA. Issue 7 (6th June 2014) - Rezaee, Mohammad; Hunting, Darel J.; Sanche, Léon
Abstract : Purpose: The present study introduces a new method to establish a direct correlation between biologically related physical parameters (i.e., stopping and damaging cross sections, respectively) for an Auger‐electron emitting radionuclide decaying within a target molecule (e.g., DNA), so as to evaluate the efficacy of the radionuclide at the molecular level. These parameters can be applied to the dosimetry of Auger electrons and the quantification of their biological effects, which are the main criteria to assess the therapeutic efficacy of Auger‐electron emitting radionuclides. Methods: Absorbed dose and stopping cross section for the Auger electrons of 5–18 eV emitted by 125 I within DNA were determined by developing a nanodosimetric model. The molecular damages induced by these Auger electrons were investigated by measuring damaging cross section, including that for the formation of DNA single‐ and double‐strand breaks. Nanoscale films of pure plasmid DNA were prepared via the freeze‐drying technique and subsequently irradiated with low‐energy electrons at various fluences. The damaging cross sections were determined by employing a molecular survival model to the measured exposure–response curves for induction of DNA strand breaks. Results: For a single decay of 125 I within DNA, the Auger electrons of 5–18 eV deposit the energies of 12.1 and 9.1 eV within a 4.2‐nm 3 volume of a hydrated or dry DNA, which results in the absorbed doses of 270 and 210 kGy, respectively. DNA bases have a major contribution to the deposited energies. Ten‐electronvolt and high linear energy transfer 100‐eV electrons have a similar cross section for the formation of DNA double‐strand break, while 100‐eV electrons are twice as efficient as 10 eV in the induction of single‐strand break. Conclusions: Ultra‐low‐energy electrons (<18 eV) substantially contribute to the absorbed dose and to the molecular damage from Auger‐electron emitting radionuclides; hence, they should be considered in the dosimetry calculation of such radionuclides. Moreover, absorbed dose is not an appropriate physical parameter for nanodosimetry. Instead, stopping cross section, which describes the probability of energy deposition in a target molecule can be an appropriate nanodosimetric parameter. The stopping cross section is correlated with a damaging cross section (e.g., cross section for the double‐strand break formation) to quantify the number of each specific lesion in a target molecule for each nuclear decay of a single Auger‐electron emitting radionuclide.